Performance Evaluation of Bus Rapid Transit (BRT) Trans Medan and Service Analysis Using the Customer Satisfaction Index (CSI) Method - P Sinaga, Agusniko; Mudiyono, Rachmat; Wibowo, Kartono (CV. Publikasi Indonesia, 2025)
Medan City as a metropolitan city has a high level of urbanization, a significant growth rate and a continuously increasing volume of vehicles every year. This causes traffic congestion, increased travel time and energy waste. Due to these problems, the Medan city government uses Bus Rapid Transit (BRT) to reduce the congestion that occurs. The operational performance and quality of BRT services are the main keys to attracting people to switch from private vehicles to public transportation. This research was conducted on the Trans Medan BRT Corridor K2 J-City – Merdeka Square. Data collection was carried out by field surveys and distributing questionnaires to Trans Medan BRT users and four experts. This study uses the provisions of the Decree of the Director General of Land Transportation No. 687 of 2002, Regulation of the Minister of Transportation of the Republic of Indonesia No. 10 of 2012, Regulation of the Minister of Transportation of the Republic of Indonesia No. 98 of 2013 and The BRT Standard 2016 for operational performance evaluation and uses the customer satisfaction index approach and analytical hierarchy process for service analysis. The results of the study showed an average load factor of 21%, an average travel time of 15.35 minutes, an average waiting time of 7.4 minutes, an average circulation time of 1.2 hours, an average speed of 25.5 km/h and a total score based on The BRT Standard 2016 of 38, which means this corridor has not met the minimum requirements for the bronze-standard BRT category. CSI analysis showed that 85.18% of Trans Medan BRT users felt very satisfied with the quality of service. Furthermore, AHP analysis identified the main factors that influence the priority of Trans Medan BRT service performance, including the ability to provide the best service to passengers, the availability of insurance or safety guarantees, comfort, responsive and appropriate service, and officers ready on site when needed.